Analisis Pelaksanaan Microteaching Mahasiswa Program Studi Pendidikan Agama Islam - Khuriyah Khuriyah (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2017)
The problem in this research is the implementation of microteaching in PAI departementÂ  FITK IAIN Surakarta has not been evaluated and need to know the urgency after the existence of several courses of learning strategy that is substantially the same as the implementation of microteaching activities.The research method used is descriptive, carried out for three months since April-June 2016. The population of this research is the students of semester V of academic year 2015/2016 that follow the microteaching of 450 students, the research sample is 260 students. The results show that: 1) The implementation of microteaching as a whole has fulfilled the provisions of microteaching implementation as stated in the microteaching guide book. Each student performs teaching practice as much as 4-5 times, previously required to prepare RPP which will be reviewed and corrected by supervisor (DPL). In implementing the teaching practice, students are required to practice one of the teaching strategies in accordance with the material to be submitted; 2) Although the students have obtained several courses of instructional strategies that note more of the practice of teaching both groups and individuals, but 81% of students stated that microteaching is still needed.Â Keywords: Analysis, Microteaching.